Evaluating the Effects of a Deep-Water Marine Protected Area a Decade After Closure: A Multifaceted Approach Reveals Equivocal Benefits to Reef Fish Populations - Runde, Brendan J.; Buckel, Jeffrey A.; Rudershausen, Paul J.; Mitchell, Warren A.; Ebert, Erik; Cao, Jie; Taylor, J. Christopher (Frontiers in Marine Science, 2021)
Marine protected areas (MPAs) are increasingly used to rebuild fish populations. In 2009, eight MPAs were designated off the southeast United States with the goal of rebuilding populations of long-lived deep-water reef fishes. We tested whether reef fish within the largest of these MPAs, the Snowy Wreck Marine Protected Area (SWMPA), have increased in size and abundance relative to a nearby control area and compared to pre-closure. Hurdle models fitted through Bayesian inference on echosounder data collected in 2007-2009 and 2018-2020 yielded no evidence of an MPA effect. Comparisons of catch-per-unit-effort (CPUE) of all reef fishes yielded similar null results. However, CPUE of reef species with formal stock assessments increased 47% in the SWMPA and decreased 50% in the control area. We found significant increases in mean length of red porgy (Pagrus pagrus) inside the SWMPA but not in the control area. We also found community composition changes, including shifts away from groupers (Serranidae; Epinephelinae) and towards snappers (Lutjanidae) and tilefish (Malacanthidae) in both areas, though we did not detect an MPA effect with this analysis. Our equivocal results indicate that more time and stricter enforcement may be necessary before more biological effects of the SWMPA can be detected.